ANALISIS YURIDIS PANDANGAN HUKUM POSITIF TERHADAP GANGGUAN KEJIWAAN SEBAGAI PENGHALANG PENETAPAN HAK ASUH ANAK TERHADAP IBU KANDUNG - NIM. A1012221067, AGREATY ANDINI KANIA (Fakultas Hukum Universitas Tanjungpura, 2026)
Abstract This study examines the perspective of Indonesian positive law regarding mental disorders as an impediment to the determination of child custody for biological mothers. The study aims to identify and analyze the perspective of positive law on mental disorders as a barrier to the determination of child custody for biological mothers, as well as to examine and analyze the legal consequences when child custody is granted to the father due to the mother’s mental health condition. This research employs a normative juridical research design with a descriptive-analytical approach, conducted through the examination of statutory regulations, legal concepts, and relevant literature. The research data are derived from primary, secondary, and tertiary legal materials, which are comprehensively analyzed to interpret legal norms, the principle of the best interests of the child, and the principle of non-discrimination. The analysis is carried out qualitatively and descriptively by considering the relevance of legal norms to child custody determination practices in the context of mental disorders. The findings indicate that mental disorders cannot be regarded as an absolute ground for preventing biological mothers from obtaining child custody. The determination of custody must take into account the mother’s actual caregiving capacity, the support of the family environment, and the best interests of the child. Furthermore, the transfer of custody to the father without objective evidence of the mother’s incapacity to provide care may result in legal consequences, including limitations on the child’s emotional relationship with the mother and the potential for discrimination against individuals with mental disorders. Therefore, the application of positive law requires proportional and evidence-based assessments in determining child custody. Keywords: juridical; law; positive; mental; determination. Abstrak Penelitian ini membahas pandangan hukum positif Indonesia terhadap gangguan kejiwaan sebagai penghalang penetapan hak asuh anak terhadap ibu kandung. Penelitian ini bertujuan untuk mengetahui dan menganalisis pandangan hukum positif terhadap gangguan kejiwaan sebagai penghalang penetapan hak asuh anak terhadap ibu kandung, serta untuk mengetahui dan menganalisis akibat hukum apabila hak asuh anak diberikan kepada ayah akibat kondisi gangguan kejiwaan ibu kandung. Penelitian ini menggunakan jenis penelitian yuridis normatif dengan pendekatan deskriptif-analitis, melalui studi perundang-undangan, konsep hukum, dan literatur terkait. Data penelitian bersumber dari bahan hukum primer, sekunder, dan tersier, yang dikaji secara komprehensif untuk menafsirkan norma hukum, asas kepentingan terbaik bagi anak, serta prinsip nondiskriminasi. Analisis dilakukan secara deskriptif kualitatif dengan mempertimbangkan relevansi norma hukum terhadap praktik penetapan hak asuh dalam konteks gangguan kejiwaan. Hasil penelitian menunjukkan bahwa gangguan kejiwaan tidak dapat dijadikan alasan absolut untuk menghalangi ibu kandung memperoleh hak asuh anak. Penetapan hak asuh harus mempertimbangkan kemampuan pengasuhan ibu secara nyata, dukungan lingkungan keluarga, dan kepentingan terbaik bagi anak. Selain itu, pengalihan hak asuh kepada ayah tanpa bukti ketidakmampuan pengasuhan yang objektif dapat menimbulkan dampak hukum berupa pembatasan hubungan emosional anak dengan ibu serta potensi diskriminasi terhadap penyandang gangguan kejiwaan. Dengan demikian, penerapan hukum positif menuntut penilaian proporsional dan berbasis bukti dalam menetapkan hak asuh anak. Kata kunci: yuridis; hukum; positif; kejiwaan; penetapan.